2019
DOI: 10.1039/c9cy00464e
|View full text |Cite
|
Sign up to set email alerts
|

On isothermality in some commonly used plug flow reactors for X-ray based investigations of catalysts

Abstract: We compare two reactor setups commonly used to make operando measurements of catalyst behavior using X-rays in terms of the degree to which they may be considered to yield radial and axial isothermality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Critically, isothermality within a reactor bed must be achieved to an acceptable degree in order to avoid thermal gradients yielding incorrect or misleading results from what are either, point measurements made within the body of a much larger sample, or measurements that report an average view over a large (a few millimetres) portion of a sample bed. 89 In the case of the use of synchrotron radiation, there is also the possibility that the X-rays themselves may induce unwanted changes in the systems under study, either through local heating effects, or from the production of electrons. Both of these possibilities have the potential to promote reduction of Cu(II) to Cu(I) wherein none should ordinarily occur.…”
Section: Experimental Considerations For In Situ Study and The Derivamentioning
confidence: 99%
“…Critically, isothermality within a reactor bed must be achieved to an acceptable degree in order to avoid thermal gradients yielding incorrect or misleading results from what are either, point measurements made within the body of a much larger sample, or measurements that report an average view over a large (a few millimetres) portion of a sample bed. 89 In the case of the use of synchrotron radiation, there is also the possibility that the X-rays themselves may induce unwanted changes in the systems under study, either through local heating effects, or from the production of electrons. Both of these possibilities have the potential to promote reduction of Cu(II) to Cu(I) wherein none should ordinarily occur.…”
Section: Experimental Considerations For In Situ Study and The Derivamentioning
confidence: 99%
“…= 2.2 mm) capillary. The sample was then mounted within a reactor system based on the design due to Chupas et al 59 that we have demonstrated 60 to yield an isothermal region twice the length of the sample bed and, therefore, to be appropriate to the kinetic study of these materials. All gases were of a high purity and flowed through scrubbers, as appropriate for each gas, to remove any residual oxygen and moisture prior their being passed through mass flow controllers (20 ml min À1 all gases).…”
Section: Sample Presentation and Reaction Protocolsmentioning
confidence: 99%
“…To meet the requirements for operando catalysis studies, particularly the need for a gas-tight system and controlled environment, a quartz capillary reactor was chosen as the primary sample holder. Such capillary reactors are analogous to those used in many conventional XAS or XRD studies using synchrotron radiation [44]. A tube or rod (support) made of glassy carbon is positioned parallel to the capillary sample holder.…”
Section: Design Of the Arctic Setupmentioning
confidence: 99%
“…An appropriate gas delivery system, such as thermal mass flow controllers, allows precise control of gas composition, flow rate, and space velocity analogously to conventional XAS or XRD studies in capillaries. Two hot air blowers positioned on either side of the sample were chosen to allow relatively uniform heating, analogous to those used in conventional XAS and XRD studies [44]. Particular care must be taken when using aRCTIC to ensure uniform heating is applied to the sample during rotation and for extended periods of tomography data acquisition.…”
Section: Design Of the Arctic Setupmentioning
confidence: 99%